2014
DOI: 10.1111/jth.12674
|View full text |Cite
|
Sign up to set email alerts
|

A role for arginine‐12 in thrombin–thrombomodulin‐mediated activation of thrombin‐activatable fibrinolysis inhibitor

Abstract: To cite this article: Plug T, Kramer G, Meijers JCM. A role for arginine-12 in thrombin-thrombomodulin-mediated activation of thrombinactivatable fibrinolysis inhibitor. J Thromb Haemost 2014; 12: 1717-25.Summary. Background: Thrombin-activatable fibrinolysis inhibitor (TAFI) is a proenzyme that links coagulation and fibrinolysis. TAFI can be activated by thrombin, the thrombin-thrombomodulin complex and plasmin through cleavage of the first 92 amino acids from the enzyme. In silico analysis of the TAFI sequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 22 publications
(34 reference statements)
3
18
0
Order By: Relevance
“…1B, lanes 2-7). These results are in line with the data reported by Plug et al [18] and Wu et al [19], demonstrating that several positively charged residues (Arg12 [18] and Lys42-Lys44 [19]) within the globular structure of the activation peptide might be important for the activation of TAFI by thrombin-thrombomodulin. Indeed, lack of the globular structure in the deletion mutant prevents efficient interaction with thrombomodulin, thereby abolishing the cofactor function.…”
Section: Results and Conclusionsupporting
confidence: 92%
See 1 more Smart Citation
“…1B, lanes 2-7). These results are in line with the data reported by Plug et al [18] and Wu et al [19], demonstrating that several positively charged residues (Arg12 [18] and Lys42-Lys44 [19]) within the globular structure of the activation peptide might be important for the activation of TAFI by thrombin-thrombomodulin. Indeed, lack of the globular structure in the deletion mutant prevents efficient interaction with thrombomodulin, thereby abolishing the cofactor function.…”
Section: Results and Conclusionsupporting
confidence: 92%
“…These results are in line with the data reported by Plug et al . and Wu et al . , demonstrating that several positively charged residues (Arg12 and Lys42–Lys44 ) within the globular structure of the activation peptide might be important for the activation of TAFI by thrombin–thrombomodulin.…”
Section: Results and Conclusionmentioning
confidence: 90%
“…In the current study, a complete TAFI fragmentation pattern analysis in the presence of different TAFI activators demonstrated that VHH-i83 only inhibits T/TM-mediated TAFI activation, indicating that VHH-i83 interferes with the cofactor function of thrombomodulin. The TAFI-VHH-i83 structure suggests that VHH-i83 sterically interferes with thrombomodulin binding by interacting with Arg12 in the AP, which substantiates findings in previous mutagenesis studies that Arg12 is a critical residue for thrombomodulin-dependent TAFI activation by thrombin [31,32]. We also observed that VHH-i83 did not inhibit thrombin-mediated cleavage of the deletion mutant TAFI-ACIIYQ-Δ 1-73 (data not shown).…”
Section: Discussionsupporting
confidence: 90%
“…This result is in agreement with the structure of TAFI-VHH-i83. Specifically, the interaction interface on the AP is in close proximity to Arg12 and Lys42-Lys44 (shortest distance: 3.6 A between atoms of Arg12 and Lys42), previously shown to constitute the thrombomodulin-binding site [30][31][32], thus indicating that VHH-i83 prevents the interaction with thrombomodulin.…”
Section: Mechanism Of Inhibition Of Tafi Activation By Vhh-i83mentioning
confidence: 94%
“…Recently, we published a study that showed that Arg12 of TAFI plays an important role in thrombin‐thrombomodulin‐mediated TAFI activation, but that it is not relevant for TAFI activation by thrombin alone . In this study we have not determined whether cleavage at Arg12 or binding to Arg12 is important for thrombomodulin‐mediated TAFI activation.…”
Section: Discussionmentioning
confidence: 93%